Comparative evaluation of novel screening strategies for colorectal cancer screening in China (TARGET-C): a study protocol for a multicentre randomised controlled trial. Issue 4 (20th April 2019) - Chen, Hongda; Li, Ni; Shi, Jufang; Ren, Jiansong; Liu, Chengcheng; Zhang, Yueming; Jiang, Zheng; Zhang, Zhihui; Dai, Min
Abstract : Introduction: Screening for colorectal cancer (CRC) is effective in reducing the disease burden. However, high-level evidence from randomised controlled trials on the effectiveness of CRC screening modalities is still lacking. We will conduct a large-scale multicentre randomised controlled trial in China to evaluate the effectiveness and cost-effectiveness of different CRC screening strategies. Methods and analysis: 20 000 eligible participants aged 50–74 years are enrolled in five provinces in China. After providing signed informed consent, the participants will be randomised into one of the three screening groups: (1) one-time colonoscopy (n=4000), (2) annual faecal immunochemical test (FIT) (n=8000) and (3) annual risk-adapted screening strategy (n=8000). The risk-adapted screening strategy will use an established CRC risk scoring system, the Asia-Pacific Colorectal Screening score. Participants at high risk of CRC will be referred for colonoscopy, while participants at low risk will be referred for an FIT. Information on clinical reports, epidemiological risk factors and health economic factors will be collected and stored in a web-based data management system. We will further request the participants to donate blood, faecal and saliva samples before conducting the colonoscopy. The primary outcome will be the detection rate of advanced colorectal neoplasia and the secondary outcomes will include the rates of CRC-related mortality, incidence of CRC, participation and complications. The study will last for at least 4 years and the cohort will be followed for 10 years to adequately answer the scientific questions. Ethics and dissemination: This study was approved by the Ethics Committee of the National Cancer Center/Cancer Hospital, the Chinese Academy of Medical Sciences and Peking Union Medical College (18-013/1615). The results of the study will be submitted for publication in peer-reviewed journals and will be discussed by policy and decision makers. Trial registration number: ChiCTR1800015506.